Clostridium perfringens Sepsis and Fetal Demise after Genetic Amniocentesis - Nancy W. Hendrix; A. Dhanya Mackeen; Stuart Weiner (Thieme Medical Publishers, Inc., 2011)
Clostridium perfringens is a rare cause of intrauterine infection. There have been five case reports concerning infection associated with invasive procedures. We report a woman who underwent a genetic amniocentesis due to her history of chronic granulomatous disease. She presented to the hospital ~38 hours after the amniocentesis complaining of fever and chills. Due to acute decompensation, she underwent an emergent dilatation and evacuation. During her stay, blood cultures came back positive for C. perfringens. Gradual improvement with intensive monitoring led to hospital discharge 4 days after the procedure. Uterine infection due to C. perfringens leading to maternal sepsis is associated with a high morbidity and mortality rate. Our patient was able to survive without a hysterectomy due to the rapid administration of antibiotics and surgical intervention while being evaluated.